Abdul Latief Hendraningrat, sang pengibar bendera pusaka 17 Agustus 1945 - Sandjojo, Nidjo 1952- (Pustaka Sinar Harapan, 2011)
Biography of Abdul Latief Hendraningrat, a nationalist behind the Indonesian proclamation of independence on August 17, 1945 in Jakarta.